Análise bioquímica da niclosamida no metabolismo de cisticercos de Taenia crassiceps - Costa, Marco Vítor Silva de Melo (2015)
Experimental studies with Taenia crassiceps have been used to demonstrate its metabolic alterations in biochemical pathways (energetic and respiratory) in response to the presence of drugs. The use of T. crassiceps as an experimental model offers conditions to reproduce the neurocysticercosis infection one of the most severe form of human cysticercosis. This study aimed the analysis of the in vitro influence of niclosamide, an antihelminthic drug, on the metabolism of carbohydrates and fatty acids of T. crassiceps cysticerci (ORF strain). 20 larval stage cysticerci were cultured into 5mL of RPMI (Gibco) supplemented culture media, in 6 well culture plates, exposed or not to niclosamide (1, 2, and 3 uM). The control groups were performed with cysticerci not exposed to the drug, exposed to ethanol in the concentration used to dissolve the drug. The cysticerci were cultured at 37ºC for 24 hours. After this period the cysticerci were removed from the culture medium and both were frozen with liquid nitrogen. Afterward, the samples were processed for the HPLC analysis. Accordingly to the mode of action of this drug, which is to interfere in the electrons chain transport, the succinate concentrations were altered in the secretion/excretion of this parasite. Therefore, it is possible to conclude that in the concentrations used, this drug caused little alteration in the metabolic pathways of the parasite.